2016
DOI: 10.1088/1758-5090/8/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different bioinks for 3D bioprinting of fibrocartilage and hyaline cartilage

Abstract: Cartilage is a dense connective tissue with limited self-repair capabilities. Mesenchymal stem cell (MSC) laden hydrogels are commonly used for fibrocartilage and articular cartilage tissue engineering, however they typically lack the mechanical integrity for implantation into high load bearing environments. This has led to increased interested in 3D bioprinting of cell laden hydrogel bioinks reinforced with stiffer polymer fibres. The objective of this study was to compare a range of commonly used hydrogel bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
262
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(291 citation statements)
references
References 64 publications
(28 reference statements)
13
262
0
6
Order By: Relevance
“…The 3D bioplotter from RegenHU (3D Discovery, Switzerland) was used for printing of alginate-ECM bioinks using previously established settings (Daly, Critchley, Rencsok, & Kelly, 2016). PCL with a molecular weight of 45.000 (Sigma-Aldrich, Ireland) was first melted at 70°C in the printing chamber.…”
Section: Bioprintingmentioning
confidence: 99%
“…The 3D bioplotter from RegenHU (3D Discovery, Switzerland) was used for printing of alginate-ECM bioinks using previously established settings (Daly, Critchley, Rencsok, & Kelly, 2016). PCL with a molecular weight of 45.000 (Sigma-Aldrich, Ireland) was first melted at 70°C in the printing chamber.…”
Section: Bioprintingmentioning
confidence: 99%
“…It was found that alginate and agarose were suitable for hyaline-like cartilage fabrication, while GelMA and BioINK TM for the formation of fibrocartilage-like tissue. Moreover, MSCs encapsulated in all the constructs showed the viability of above 80% [61]. As shown in Fig.…”
Section: Bioprinting Of Cartilagementioning
confidence: 71%
“…It was demonstrated that the hydrogels could direct cell migration, chondrocytes moving to hyaluronic acid, while osteoblasts migrating to type I collagen [60]. Daly et al [61] aimed to screen out proper hydrogels to induce bone marrow stem cells (BMSCs) to differentiate toward cartilage. The commonly used hydrogels including agarose, alginate, GelMA and BioINK TM were employed to construct cartilage structures.…”
Section: Bioprinting Of Cartilagementioning
confidence: 99%
“…Cell viability during 3D bioprinting is dependent on the shear stress experienced during extrusion, which in turn is dependent on the viscosity of the solution, the applied pressure, and the needle diameter. In addition, any post-printing bioink cross-linking may also impact on cell viability [62]. Cell viability can be measured with Live/Dead Viability/ Cytotoxicity assay after printing [63] and could vary with dispensing pressure and nozzle diameter.…”
Section: Scaffold Biodegradability and Cell Viabilitymentioning
confidence: 99%